Produção de cefamicina C por Streptomyces clavuligerus em batelada e batelada alimentada - Bellão, Carolina (2010)
Cephamycin C (CephC) is a natural antibiotic produced by Streptomyces clavuligerus that presents β-lactamases resistance, enzymes that clives β-lactam of antibiotics. The aim of present work was study cephamycin production by Streptomyces clavuligerus in batch and fed-batch cultivations, in order to define important parameters as culture medium and carbon source feeding conditions for the purpose of maximize the CefC production. First the methodology of analysis of CefC was tested. Due to standard unavailability for analysis of CefC in the fermentative broths, it was evaluated the sensibility of microorganism test (Escherichia coli ESS) face other standards. It was verified that E. coli ESS strain presents super sensibility to penicillin G and cephalosporin C. Due to the presence of clavulanic acid (CA) in the both, a β-lactamase inhibitor, it was evaluated the influence of the sample treatment (acid and basic hydrolisis) on penicillin N hydrolysis by penicillinase. For an adequate CephC analysis, the results showed that both clavulanic acid and cephamycin C were degraded in acid and alkaline medium, with higher degradation was in alkaline pH. The results show that the samples should be treated only with penicillinase for the correct CephC analysis by elimination of intermediates compounds the CephC biosynthetic pathway. For the evaluation of the CephC production, firstly different culture media proposed in the literature were tested with S. clavuligerus ATCC 27064 strain in bench scale bioreactor. The best result in terms of cellular growth and CephC production (374.8 mg.L-1 em 66 h) was obtained in batch cultivation that utilized starch and cottonseed meal as carbon and nitrogen sources. The influence of carbon and nitrogen sources on CephC production was then evaluated utilizing two Streptomyces clavuligerus strains, ATCC 27064 and DSM 41826, a natural mutant indicated as higher CephC producing by literature. Glycerol and soy bean meal have showed more suitable as carbon and nitrogen sources for CephC production due probably to slow and gradual availability of nitrogen from protein hydrolysis of soy bean meal (insoluble nitrogen source). In the fed-batch cultivation utilizing glycerol or starch as carbon source, the best result in terms of CephC production (566.5 mg.L-1 in 108 h) was obtained in the fed-batch cultivation with glycerol feeding at volumetric flow rate of 0,01 L.h-1 and concentration of 177 g.L-1. In the experimental conditions tested in the fed-batch cultivations, ranging carbon source and feeding conditions, it was not possible visualize the dissociation between clavulanic acid and cephamycin productions. The higher CephC in medium with glycerol is probably associated to its favorable energetic balance and metabolization rate in relation to starch.